Tutorials in Bioinformatics for Biological Science [editorial] - Vitorino, R. (2019)
One of the major challenges of the past few years is the integration of Omics data to disclose its biological meaning. With the advances in Omics technologies the complexity and amount of retrieved data has increased, making difficult and time-consuming its integrative analysis. Even so, the integration of a wide spectrum of Omics data sets is essential to promote translational research. Bioinformatics tools allow to mine information from large databases obtained from robust platforms of Genomics, Proteomics, Metabolomics, among others in a system biology perspective. From this point of view, several bioinformatics tools are proposed in this special issue - Bioinformatics - of Journal of Proteomics to attain and integrate different kinds of Omics information. The central idea of this issue is the promotion of how to do it, showing the pipeline from data into their analysis as well their interpretation. Several researchers with recognized expertise in the field of Omics, mainly devoted toward mass spectrometry, were invited to contribute with tutorials that intend to help academics and partners from industry to apply bioinformatics tools to, for example, elucidate the glycan structure or study complex microbial communities.